Kamuflaż kontra honor - Kulisz, Marek (Er(r)go. Teoria - Literatura - Kultura, 2007)
Marek Kulisz Camouflage versus Honour The idea of camouflage stands in opposition to chivalry, and in particular in opposition to honour and courage. For ages knights and warriors wanted to be seen and recognized, as they could not win fame and glory by hiding and outsmarting their enemy. Surprise attacks carried out from hiding were the domain of highwaymen and other kinds of dishonourable riffraff. The appearance of camouflage, though gradual, marks a change in our civilization's perception of warfare, and perhaps conflict in general, when it became more important to be cunning and efficient rather than honourable and brave.